The hepatoprotective effects of dihydromyrcenol and geranyl formate in an experimental model of acute hepatic injury induced by the use of carbon tetrachloride - İrfan BAYRAM,; Remzi ERTEN,; Yasemin BAYRAM,; Gülay BULUT,; Hanefi ÖZBEK, (Turkish Journal of Gastroenterology, 2019)
-